Transseptal Dispersion of Repolarization and Its Role in the Development of Torsade de Pointes Arrhythmias - Sicouri, Serge (2009)
OBJECTIVE: This study was designed to quantitate transseptal dispersion of repolarization (DR) and delineate its role in arrhythmogenesis using the calcium agonist BayK 8644 to mimic the gain of function of calcium channel current responsible for Timothy syndrome. BACKGROUND: Amplification of transmural dispersion of repolarization (TDR) has been shown to contribute to development of Torsade de Pointes (TdP) arrhythmias under long-QT conditions. METHODS: An arterially-perfused septal wedge preparation was developed via cannulation of the septal artery. Action potentials (APs) were recorded using floating microelectrodes together with a transseptal electrocardiogram (ECG). These data were compared to those recorded from arterially-perfused canine left ventricular (LV) wedge preparations. RESULTS: Under control conditions, the shortest AP duration measured at 90% repolarization (APD(90)) was observed in right ventricular (RV) endocardium (181.8±15 ms), APD(90) peaked close to mid-septum (278.0±32 ms), and abbreviated again as LV endocardium was approached (207.3±9 ms). Transseptal DR averaged 106±24 ms and T(peak)-T(end) 84±7 ms (n=6). TDR and T(peak)-T(end) recorded from LV wedge were 36±9 ms and 34±19 ms, respectively (n=30). BayK 8644 increased transseptal DR to 123.2±35 ms (n=5) and induced early and delayed afterdepolarizations (3/5), rate-dependent ST-T-wave alternans (5/5), and TdP arrhythmias (3/5). CONCLUSIONS: Our data indicate that dispersion of repolarization across the interventricular septum is twice that of the LV free wall, predisposing to development of TdP under long-QT conditions. Our findings suggest that the coronary-perfused ventricular septal preparation may be a sensitive model in which to assess the potential arrhythmogenic effects of drugs and pathophysiological conditions.